Adherence to guidelines for natriuretic peptide testing in heart failure: a nationwide survey of healthcare professionals in Vietnam - Thanh Huong Truong; Doan-Loi Do; Ngoc-Thanh Kim; Nguyen-Son Pham; Quynh-Nga Vu; Anh-Tien Hoang; Van-Sy Hoang; Minh-Tuan Pham; Phuong-Anh Nguyen; The-Anh Le; Ngoc-Anh Thi Tran; Thanh-An Le; et al. (BMJ Open)
Objectives This study aimed to determine doctors’ level of adherence to the natriuretic peptide testing guideline and to identify the factors influencing their adherence.Design Cross-sectional study.Setting Web-based survey.Participants Full-time doctors involved in heart failure (HF) treatment in Vietnam.Primary and secondary outcome measures Doctors using natriuretic peptide testing for diagnosis, differential diagnosis, treatment assessment and prognosis of patients with HF were classified as adhering to the guidelines. We assessed the practice of natriuretic peptide testing and stratified the doctors based on their professional qualifications. Univariate and multivariate logistic regression analyses were used to estimate the Odds Ratio (ORs) and 95% CIs for associations between guideline adherence and selected covariates.Results Over half of the participants adhered to the natriuretic peptide testing guidelines (57.4%). Cardiologists adhered more closely to the guidelines than other professionals; they had approximately four times higher odds of adherence than other doctors (univariate model, OR: 3.88, 95% CI: 2.56 to 5.89, p<0.001; multivariate model, OR: 4.24, 95% CI: 2.64 to 6.82, p<0.001). Cardiologists also had significantly higher rates of using natriuretic peptide testing for diagnosis (93.8% vs 84.1%, p<0.002), differential diagnosis (71.4% vs 53.5%, p<0.001), treatment assessment (87% vs 64.2%, p<0.001) and prognosis (68.2% vs 50.4%, p<0.001) than other professionals. More years of professional experience correlated with higher guideline adherence (<2 years was used as a reference point; >5 to <10 years, OR: 2.59, 95% CI: 1.45 to 4.60, p<0.001; ≥10 years, OR: 2.30, 95% CI: 1.30 to 4.09, p<0.004).Conclusion The level of adherence to natriuretic peptide testing guidelines among doctors treating patients with HF varies across Vietnam. Targeted interventions are needed to enhance understanding and proficiency, especially among non-cardiologists and those with limited experience. A dedicated fact sheet focusing on natriuretic peptide testing in HF management, separate from the existing guidelines, could bridge this gap.